Choice and evaluation of hospitals in Bangladesh: insights from patients and policy implications - Andaleeb, Syed Saad (© University of North Carolina at Chapel Hill. Dept. of Health Policy & Administration., 2016)
This is an Open Access Article. It is published by Journal of Health & Population in Developing Countries.and the definite version is available at : http://doi.org/10.12927/whp..17491 The Journal's Retrieved from https://www.researchgate.net/publication/11117851